Demographics, risk factors, and complication or readmission rates after multiligament knee reconstruction: A retrospective cohort study. Issue 1 (19th January 2020) - Sivasundaram, Lakshmanan; Paliobeis, Andrew; Labelle, Mark W.; Kim, Chang-Yeon; Trivedi, Nikunj N.; Karns, Michael J.; Salata, Michael J.; Voos, James E.
Abstract : Background: Multi-ligament knee injuries are complex and relatively rare injuries. As a result outcome data available to guide treatment are limited, and management strategies often are debated. Methods: Patients who underwent multiligament knee reconstructions between 2005 and 2015 were identified in the National Surgical Quality Improvement Program (NSQIP) database using validated CPT codes. Thirty-day complication and readmission rates after multiligament knee repair or reconstruction were identified. A multivariable logistic regression model was then used to identify statistically significant associations between patient factors and outcomes. Results: We identified 481 patients with an average age of 30.1±14.9 yr, and 67.2% male predominance. Using the American Society of Anesthesiologists (ASA) classification system, 222 patients (46.2%) were "Healthy" (ASA 1), 218 patients (45.3%) had "Mild Systemic Disease" (ASA 2), and 38 (7.9%) patients had "Severe Systemic Disease" (ASA 3). Of the sample 96.3% underwent multiligament knee reconstruction on an outpatient basis with 75.9% (365 patients) of the procedures performed in an outpatient surgery center. At 30-days postoperatively, the sample had a 6.2% overall complication rate; 4.8% of patients had a minor complication, and 1.5% of patients had a major complication. The most common minor and major complications were superficial surgical site infection and pulmonary embolus, respectively. Conclusions: Multiligament knee injuries commonly occur in young, relatively healthy individuals. This study indicates that reconstructive procedures are quite safe and supports the premise that multiligament knee reconstructions can be safely performed even as an outpatient. Level of Evidence: Level III.